2015
DOI: 10.1371/journal.pntd.0004112
|View full text |Cite
|
Sign up to set email alerts
|

Brucellosis and Coxiella burnetii Infection in Householders and Their Animals in Secure Villages in Herat Province, Afghanistan: A Cross-Sectional Study

Abstract: BackgroundBrucellosis and coxiellosis are known to be endemic in ruminant populations throughout Afghanistan, but information about their prevalence and factors that affect prevalence in householders and livestock under diverse husbandry systems and pastoral settings is sparse.Methods/Principal FindingsWe conducted a cross-sectional survey to investigate the seroprevalence of brucellosis and Coxiella burnetii in humans and livestock in six secure districts in Herat from 26th December 2012–17th January 2013. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 20 publications
4
23
1
Order By: Relevance
“…About 4.96% prevalence of brucellosis has been reported among PUO and occupationally exposed individuals in Goa [18], 24.5% in Ludhiana, India [19]. Globally several studies showed the similar seroprevalence such as 6.4% in Iran [20], 5.2% in Afghanistan [21], 3.4% in Central Anatolia [22], 19% in Saudi Arabia [23], 53.25% in Mongolia [24], 20.5% in Tanzania [25], 6.26% in Egypt [26], 16% in Kenya [27], 2.15% in Ethiopia [28], 24.1% in abbatoir workers of Abuja [29], 17% in Uganda [30] and 3.8% in Chad [31].…”
Section: Discussionmentioning
confidence: 94%
“…About 4.96% prevalence of brucellosis has been reported among PUO and occupationally exposed individuals in Goa [18], 24.5% in Ludhiana, India [19]. Globally several studies showed the similar seroprevalence such as 6.4% in Iran [20], 5.2% in Afghanistan [21], 3.4% in Central Anatolia [22], 19% in Saudi Arabia [23], 53.25% in Mongolia [24], 20.5% in Tanzania [25], 6.26% in Egypt [26], 16% in Kenya [27], 2.15% in Ethiopia [28], 24.1% in abbatoir workers of Abuja [29], 17% in Uganda [30] and 3.8% in Chad [31].…”
Section: Discussionmentioning
confidence: 94%
“…Brucellosis remains a persistent zoonotic infection mainly caused by B. abortus and B. melitensis in ruminants in Pakistan and neighboring countries [25][26][27][28][29][30][31][32][33]. Canine brucellosis (B. canis) has also been reported in surrounding countries [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…Later, 0.5 ml of phenol was added in this mixture. The mixture was autoclaved for (20) minutes at 121 0 C and the solution was kept for examination of antibody titer for serum agglutination test. About 0.8 ml of phenol saline was added in labeled tubes followed by the addition of 0.2 ml serum sample and was mixed thoroughly but gently (1/5 dilution).…”
mentioning
confidence: 99%